Microfinance Bank’s Loans and Micro, Small and Medium Enterprises Financial Performance in Ota Town Ogun State - Adurayemi, Adu Cecilia; Chigo, Uchehara Chris (MultiTech Publisher, 2023)
This study evaluated the effect of microfinance bank’s loans on the micro, small and medium scale enterprises financial performance in Ota. The population of the study was five (5) micro, small and medium scale enterprises who were customers of Covenant Microfinance Bank. Regression analysis was used to analyze the two hypotheses. It was found out that microfinance bank’s loans have positive and significant relationship with the financial performance of (MSMEs). It was recommended that microfinance banks should give more loans to (MSME) in order to improve their return on assets.